PERKEMBANGAN PROBLEMA AGRARIA DI MASA MENDATANG - Surahman Surahman; R Kunto Adi (Universitas Sebelas Maret, 2008)
In pasal 33 ayat 3 UUD 1945, the Nation has the rights to control over the agrarian objects, not to possess it. So that it must optimally manage the allocation, the stock employing and the maintenance of the agrarianobjects for the present generation as well as the future in order to achieve the prosperous society